Development and study of 28 GHz antenna for different shapes and work on antenna transparency for cellular devices - Zafar, Tanzila; Noor, Al; Ahmed, Tousif; Piya, Nure Morsalina Jannat (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.